Tuberculosis presenting as a neck abscess. (4th January 2013) - Dunphy, L.; Boyd, D.; Holland, I.
Abstract Tuberculosis is a chronic granulomatous infection caused by Mycobacterium tuberculosis and is still the most fatal infectious disease worldwide. It remains a therapeutic and diagnostic challenge because it mimics other pathological processes and yields inconsistent physical and laboratory findings. We present a case of tuberculous lymphadenitis presenting in the cervical lymph nodes of a young male.